Mobility of Zinc in Sandy Soil of Loukkos Area (northwestern Morocco) - Drissi Saad; Abdelhadi Aït Houssa; Ahmed Bamouh; Ahmed Bouaziz; Mohamed Benbella (Faculty of Agriculture, Universitas Sebelas Maret, 2016)
This study investigated the effect of different leaching rates on the downward movement of zinc applied, as fertilizer, on the surface of a sandy soil. The experiment was conducted in polyethylene bags filled to 30 cm depth with sandy soil. A zinc supply of 15.3 10-3 cmolc kg-1 was applied to the soil surface as a solution of zinc sulfate. Three leaching rates were tested: 31 mm, 208 mm and 497 mm. Results showed the absence of zinc in the leachate for all leaching rates. Within the soil profile, the highest content on exchangeable zinc (15.3 10-3 cmolc kg-1) was recorded in the top soil layer (0-10cm) for all leaching rates. In the middle (10-20 cm) and in the lower (20-30 cm) layers, the exchangeable zinc content remained similar to that recorded before leaching (0.76 10-3 cmolc kg-1). The percentage of the cation exchange capacity occupied by zinc in the top soil layer increased after leaching. It averaged 0.35% for all leaching rates while it remained similar to that recorded before leaching (0.03%) for the middle and the lower layers. This increase was linked to the adsorption saturations sites particularly released by manganese, potassium, calcium and ammonium after their downward movement.